2019
DOI: 10.3390/ani9100764
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breed and Stage of Lactation on Milk Fatty Acid Composition of Italian Goat Breeds

Abstract: Simple SummaryMilk fatty acid composition affects human health and dairy products flavor. In particular, some saturated fatty acids increase the risk of cardiovascular diseases, whereas conjugated linoleic acid inhibits carcinogenesis and reduces atherosclerosis and diabetes. Moreover, a greater amount of some short chain fatty acids increase the goaty flavor of dairy products. The objective of this study was to evaluate the breed and week of lactation effects on milk fatty acid profile of 5 Italian local goat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 56 publications
10
34
3
Order By: Relevance
“…The content of RA recorded in our study was comparable to that reported by Ayadi and Ramon (2009) and slightly higher than that reported by Shibani et al (2011). However, total CLA and RA levels were considerably higher than those reported in ruminant milk fats in various conditions (Talpur et al, 2008;Devle et al, 2012;Tudisco et al, 2019;Wang et al, 2013;Currò et al, 2019). Both RA and total CLA contents were significantly affected by the management system and the highest levels were recorded in milk from the semi-intensive system.…”
Section: Conjugated Linoleic Acids (Cla)mentioning
confidence: 71%
See 1 more Smart Citation
“…The content of RA recorded in our study was comparable to that reported by Ayadi and Ramon (2009) and slightly higher than that reported by Shibani et al (2011). However, total CLA and RA levels were considerably higher than those reported in ruminant milk fats in various conditions (Talpur et al, 2008;Devle et al, 2012;Tudisco et al, 2019;Wang et al, 2013;Currò et al, 2019). Both RA and total CLA contents were significantly affected by the management system and the highest levels were recorded in milk from the semi-intensive system.…”
Section: Conjugated Linoleic Acids (Cla)mentioning
confidence: 71%
“…The feeding system has been shown to be the main factor; in particular, pasture feeding increases the concentration of FA that are more favorable to human nutrition (Lopez et al, 2019;Chilliard et al, 2002). The profile of these FA seems to be influenced by the stage of lactation and breed (Currò et al, 2019;Bainbridge et al, 2016;Kay et al, 2005;Craninx et al, 2008). In camel, studies focusing on CLA and TFA are scarce or even non-existent in OBCFA.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to early lactation, percentage of PUFA has increased in 28th day. It has reported to decrease towards the end of the lactation in different goat breeds 24 . However, it has increased in the transition processes from colostrum to mature milk in this study.…”
Section: Resultsmentioning
confidence: 98%
“…Hence, milk has become better quality with the transition period 32 . PUFA has been reported to decrease towards the end of the lactation in different goat breeds 33 . However, it has increased in the transition processes from colostrum to mature milk in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has known that nutrition has important effects on milk fatty acid profile, studies show that the lactation period is another major point on this parameter 34 , 35 . While there have been controversial reports about fatty acid profile of milk in different lactation stages 33 , 36 , it has been showed up fatty acid profile of goat milk is one of the most variable components among the lactation period, together with milk yield and composition 35 .…”
Section: Discussionmentioning
confidence: 99%